Pengaruh Gaya Kepemimpinan dan Pelatihan Kerja Terhadap Kinerja Pegawai Dinas Pemadam Kebakaran Kota Makassar - Resti Bunga (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The objective of this research is to determine the influence of leadership style and work training variables on employee performance at the Fire Department of Makassar City. This study employs a quantitative approach using primary data obtained through questionnaires from respondents. The population in this study consists of all field officers with civil servant status at the Fire Department of Makassar City, totaling 70 employees. The sample is selected using purposive sampling, which involves selecting samples based on specific considerations that meet the desired criteria to determine the sample size to be studied. This research uses multiple linear regression analysis with SPSS 25 as the tool. The results of this study indicate that leadership style and work training have a positive and significant influence on employee performance at the Fire Department of Makassar City. Simultaneously, leadership style and work training together have an impact on employee performance at the Cultural Department of Makassar City.